Food microbiology : fundamentals and frontiers - Doyle, Michael P.; Buchanan, Robert, 1946- (Reference Manual, ASM Press., 2013)
This essential reference emphasizes the molecular and mechanistic aspects of food microbiology in one comprehensive volume.